Why Has Deep Brain Stimulation Had So Little Impact in Psychiatry? - Mocking, Roel J. T.; Graat, Ilse; Denys, Damiaan (Frontiers in Neurology, 2021)
Over two decades ago, the first scientific publication on deep brain stimulation (DBS) in psychiatry was published. The evidence for effectiveness of DBS for several psychiatric disorders has been steadily accumulating since this first report of DBS for OCD in 1999. However, the number of psychiatric patients treated with DBS is lagging behind, particularly in comparison with neurology. The number of patients treated with DBS for psychiatric indications worldwide probably does not exceed 500, compared to almost 300,000 patients with neurological disorders that have been treated with DBS in the same 20 years. It is not the lack of patients, knowledge, technology or efficacy of DBS that hinders its development and application in psychiatry. Here, we discuss the reasons for the gap between DBS in neurology and psychiatry, which seem to involve the scientific and social signature of psychiatry.